Purification of Capsular Polysaccharides of Streptococcus pneumoniae: Traditional and New Methods - Morais, Victor; Dee, Valerie; Suárez, Norma (Frontiers in Bioengineering and Biotechnology, 2018)
Pneumonia caused by Streptococcus pneumoniae is the major bacterial disease responsible for many deaths, particularly in children under 5 years of age and adults over 50. The capsular polysaccharide (CPS) constitutes the outermost layer of the bacterial cell and is the main virulence factor. Purification of CPS is essential for preparing vaccines against S. pneumoniae, whether composed of CPS alone or CPS conjugated to proteins. These vaccines are effective and safe but are quite expensive. This review describes the currently available methods of CPS purification. Advances in CPS purification methods are aimed at improved quality and yield and above all, process simplification.